2010
DOI: 10.1002/cssc.201000060
|View full text |Cite
|
Sign up to set email alerts
|

Computational Comparison of the Reactions of Substituted Amines with CO2

Abstract: Substituted amines are a popular choice as molecules to selectively react with and separate CO2 from gas mixtures. Such separations are of particular interest, for example, for CO2 separations for carbon capture and sequestration. It is desirable to tune amine–CO2 reaction energies to suit a particular separation. Herein, we use DFT‐B3LYP simulations to characterize the products and energetics of reactions of CO2 with a range of substituted amines, considering both 1:1 and 2:1 amine/CO2 reaction stoichiometrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 37 publications
(58 reference statements)
4
53
0
Order By: Relevance
“…Schneider et al [16] showed using DFT-B3LYP calculations that the reaction energies of CO 2 with amine are a function of both substituents and stoichiometry; in good agreement with the experimental findings [17], they found that a negatively charged amine reacts with CO 2 in a 1:1 ratio.…”
Section: Introductionsupporting
confidence: 58%
“…Schneider et al [16] showed using DFT-B3LYP calculations that the reaction energies of CO 2 with amine are a function of both substituents and stoichiometry; in good agreement with the experimental findings [17], they found that a negatively charged amine reacts with CO 2 in a 1:1 ratio.…”
Section: Introductionsupporting
confidence: 58%
“…According to this, different rate based models may be derived depending on the assumptions and approximations used. Currently, research effort is also being devoted to the overall reaction mechanisms involved in the CO 2 absorption into amine and its effects on the absorption efficiency (Sexton and Rochelle, 2011;Bedell, 2011;Qin et al, 2010;Mindrup and Schneider, 2010;Lepaumier et al, 2009a,b;Lepaumier et al, 2010). In addition, detailed mathematical models based on both film and penetration theories are being developed (Simon et al, 2011;Faramarzi et al, 2010;Edali et al, 2009;Zhang et al, 2009;Lawal et al, 2009;van Loo et al, 2007).…”
Section: Nomenclaturementioning
confidence: 98%
“…The phenomenon of carbonation of amines with CO 2 of air is well known [68,69]. Therefore the diamine has been previously distilled under vacuum at 120°C and stored under inert gas (Argon).…”
Section: Scheme 2: Carbonation Of Ppo-dge and Tmp-tgementioning
confidence: 99%